Diversity of Ferns (Pteridophyta) in the Bukit Pinteir Forest Central Bangka - Harijayanti, Devita; Nisa, Amanatun; Partinisah, Firgia; Salsabila, Naqqiyah; Indira, Salsa; Ramadani, Suci Hajria; Izafah, Tari Zara; Amelia, Tia (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The aim of this study was to identify and analyze the diversity of ferns (Pteridophyta) in the secondary forest of Bukit Pinteir, Central Bangka. We collected the primary data through field observations conducted using the purposive sampling method, along with the measurement of abiotic factors at two stations with different altitudes (96 and 238 mdpl). The data were analyzed with important value index and Shannon-Wiener species diversity index (H’). Twelve fern species from 10 families were identified, namely Dicranopteris linearis, Davallia denticulata, Nephrolepis cordifolia, Nephrolepis biserrata, Lygodium japonicum, Lygodium flexuosum, Coniogramme japonica, Blechnopsis orientalis, Asplenium nidus, Platycerium coronarium, Pteridium esculentum, and Stenochlaena palustris. Based on the results, Nephrolepis cordifolia was the most dominant species, with its important value index was 16.92, followed by Dicranopteris linearis and Blechnopsis orientalis. The Shannon-Wiener diversity index (H’ = 0.663) indicated low species diversity with uneven distribution. Abiotic factors such as temperature (30.1–30.5 °C), soil moisture (60–70%), air humidity (67–71%), and soil pH (6.5) reflected a microclimate favorable for fern growth. Many studies are still needed to record the diversity of ferns in Bukit Pinteir and increase species diversity to maintain environmental sustainability.